The Effect of Cooperative Integrated and Composition (CIRC) Strategy towards Students’ Reading Comprehension of Descriptive Text - Yesi Ratna Dila; Loli Safitri (Universitas Pahlawan Tuanku Tambusai, 2022)
The students of MTS TI Koto Tuo still encounter problems in mastering English especially in reading comprehension of descriptive text. This research used experimental research. The researcher used a quasi-experimental design by using the pre-test and post-test control group design. The population of this research was the Eighth grade students at MTS TI Koto Tuo. The sample was VIII.1 which was treated as experimental class and taught by using CIRC strategy and VIII.2 was treated as control class and taught by using conventional strategy. To determine the sample, the researcher used purposive sampling technique based on some consideration. From the result and accounting the pre-test and post-test scores of the experiment class, it was found that the t-obtained (7,66) was higher than the t-table (1.6787) with degree of freedom (df) = 49 and (α) = 0,05. So, the alternative hypothesis (Ha) was accepted which means that there was significant effect of CIRC strategy to the students reading comprehension on descriptive text. It is proved that using CIRC strategy as a reading strategy can help the students in improving their reading comprehensions especially descriptive text.